Extravesical vs. intravesical ureteric reimplantation for primary vesicoureteral reflux: A systematic review and meta-analysis - Law, Zhi Wei; Ong, Caroline C. P.; Yap, Te-Lu; Loh, Amos H. P.; Joseph, Udayan; Sim, Siam Wee; Ong, Lin Yin; Low, Yee; Jacobsen, Anette S.; Chen, Yong (Frontiers in Pediatrics, 2022)
Purpose This study aims to compare the outcomes of extravesical (EVUR) and intravesical (IVUR) ureteric reimplantation for primary vesicoureteral reflux (VUR) via systematic review and meta-analysis. Methods Literature review from Medline, Embase and Cochrane since inception to March 2022 was performed. Meta-analysis was conducted on eligible randomized controlled trials (RCT) and observational cohort studies (OCS) comparing outcomes between EVUR and IVUR. Results Twelve studies were included, comprising 577 patients (778 ureters) operated by EVUR and 395 patients (635 ureters) by IVUR. Pre-operative VUR grade, postoperative VUR persistence and hydronephrosis was not statistically significant. EVUR had shorter operative time (MD -22.91 min; 95% CI, -44.53 to -1.30, P = 0.04) and hospital stay (MD -2.09 days; 95% CI -2.82 to -1.36, P<0.00001) compared to IVUR. Bilateral EVUR had higher risk of postoperative acute urinary retention (ARU) (8.1%) compared to bilateral IVUR (1.7%) (OR=4.40; 95% CI 1.33-14.58, P=0.02). No patient undergoing unilateral EVUR or IVUR experienced ARU. Conclusion Both EVUR and IVUR are equally effective in correcting primary VUR. Operative time and hospital stay are shorter after EVUR compared to IVUR. However, bilateral EVUR is associated with higher risk of postoperative ARU.